The Influence of Competencies and Motivation on Employee Performance: In the Job Satisfaction Perspective - hilmi, Hilmi; Adam, Muhammad (JOURNAL OF ECONOMIC SCIENCE, 2015)
Employee job performance in an organization or company is required to contribute for the company. Competency, motivation, job satisfaction and job performance is part of human resource management which is currently a popular issue in an organization or company, both in the public and private sectors as well as widely published in journals locally and internationally. This study analyzes the supporting factors of competency, motivation and job satisfaction that affecting to job performance of employees at Aceh SMEs. This study raises some hypotheses to acknowledge the problems using survei method of 200 respondents, namely employees at Aceh SMEs, through questionnaires.The data analyzed using Structural Equation Modeling (SEM) operated by Lisrel. The results of the data analysis showed that the hypothesis is acceptable. Research shows that all the independent variables simultaneously positive and significant effect on the dependent variable. Competency has the most dominant effect on job performance when compared with the motivation and job satisfaction of employees at Aceh SMEs.